Asphaltenes as model compounds of the UIBs/AIBs detected in various astrophysical objects. Part 1 – Petroleum asphaltenes carbonization. Issue 5 (12th May 2022) - Cataldo, Franco; García-Hernández, D. Aníbal; Manchado, Arturo
Abstract: The Unidentified Infrared bands (UIBs or UIRs) known also as Aromatic Infrared Bands (AIBs) represent a series of discrete infrared emission bands detected in numerous and very different astrophysical objects. The carriers of these infrared bands have not yet unambiguously identified. The MAONs model proposes that the carriers of the UIBs could be described by an "average" chemical structure consisting of mixed aromatic-aliphatic organic nanoparticles (MAONs) and containing also heteroatoms such as N, S and O. Asphaltenes are matching quite well the MAONs model and in this work a series of selected asphaltenes from petroleum were carbonized at 700 °C in sealed crucible under inert atmosphere leading to a carbon coke. Both the starting asphaltenes and the result of their carbonization were studied with FT-IR spectroscopy. It is shown that the asphaltenes and the resulting coke can be considered excellent model compounds for the UIBs' carriers and their evolution because of thermal and radiation processing of the latter in the harsh space environment.